2009
DOI: 10.1177/0022219409338738
|View full text |Cite
|
Sign up to set email alerts
|

A Literacy Tutoring Experience for Prospective Special Educators and Struggling Second Graders

Abstract: This study examined the learning of teacher candidates taking a language arts course in a special-educator preparation program and that of the second graders they tutored in a supervised field component of the course. Teacher candidates' knowledge of literacy instruction was assessed using five knowledge tasks; children were assessed on several measures of basic reading and spelling skills as well as on their knowledge of phonics concepts such as syllable types. Teacher candidates generally had inaccurate perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 18 publications
2
59
0
Order By: Relevance
“…The PSTs’ improved level of knowledge about the structure of language was similar to gains (from a pretest mean of about 12 correct to a posttest mean of about 15 correct) found on the same 22-item test (Al Otaiba & Lake 2007; Bos et al, 2001). The magnitude of gains was similar to the magnitude of gains on slightly different tests of the same construct (McCutchen et al, 2002; Spear-Swerling, 2009; Spear-Swerling & Brucker, 2004). This increased knowledge may not be surprising given that the Early Literacy course we described had a syllabus and a text that were consistent with the NRP (2000) evidence base and the instructor, the final author of the study, was knowledgeable as well.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…The PSTs’ improved level of knowledge about the structure of language was similar to gains (from a pretest mean of about 12 correct to a posttest mean of about 15 correct) found on the same 22-item test (Al Otaiba & Lake 2007; Bos et al, 2001). The magnitude of gains was similar to the magnitude of gains on slightly different tests of the same construct (McCutchen et al, 2002; Spear-Swerling, 2009; Spear-Swerling & Brucker, 2004). This increased knowledge may not be surprising given that the Early Literacy course we described had a syllabus and a text that were consistent with the NRP (2000) evidence base and the instructor, the final author of the study, was knowledgeable as well.…”
Section: Discussionsupporting
confidence: 56%
“…Two of the three studies found a relationship between PST’s knowledge and student progress; one did not (Spear-Swerling, 2009). In the present study, we emphasized this relationship in the Early Literacy course using Gough and Tunmer’s Simple View (1986) of reading to provide preservice teachers with a useful and practical theoretical framework for understanding the importance of pedagogical knowledge in improving student progress.…”
Section: Perspectives or Theoretical Framework Of The Early Literacy mentioning
confidence: 98%
See 2 more Smart Citations
“…In our review, several studies of reading and mathematics revealed teacher educator approaches to integrating how to teach content with the procedural knowledge necessary for implementing instruction and knowledge of student performance (Alexander, Lignugaris-Kraft, & Forbush, 2007;Paulsen, 2005;Spear-Swerling, 2009;Spear-Swerling & Brucker, 2004). Mostly, these approaches involved contentfocused methods coursework combined with highly structured field experiences.…”
Section: Pedagogical Content Knowledgementioning
confidence: 99%